2014
DOI: 10.1371/journal.pone.0095261
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Based Attentional Priority for Storage in Visual Short-Term Memory

Abstract: A plethora of research demonstrates that the processing of emotional faces is prioritised over non-emotive stimuli when cognitive resources are limited (this is known as ‘emotional superiority’). However, there is debate as to whether competition for processing resources results in emotional superiority per se, or more specifically, threat superiority. Therefore, to investigate prioritisation of emotional stimuli for storage in visual short-term memory (VSTM), we devised an original VSTM report procedure using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 52 publications
(113 reference statements)
2
28
2
Order By: Relevance
“…In the present study, we have replicated these results with angry faces compared to neutral faces; we observed that facial expressions of intense anger elicited an SPCN of greater amplitude than neutral and subtle facial expressions and, moreover, were associated with greater accuracy in the change detection task when compared to the other two levels of intensity of facial expressions (neutral and subtle). This overall pattern of findings is very well in line with the benefit observed for negative and angry facial expressions in previous studies in terms of behavioral indices of sensitivity (Jackson et al , 2008 ; Langeslag et al , 2009 ; Jackson et al , 2014 ; Simione et al , 2014 ; Xie and Shang, 2016 ). An unexpected result refers to the observation that the faces with expression of subtle anger elicited not only an SPCN of lower amplitude than the faces with full expressions of anger but also an SPCN of lower amplitude than the faces with neutral expressions.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, we have replicated these results with angry faces compared to neutral faces; we observed that facial expressions of intense anger elicited an SPCN of greater amplitude than neutral and subtle facial expressions and, moreover, were associated with greater accuracy in the change detection task when compared to the other two levels of intensity of facial expressions (neutral and subtle). This overall pattern of findings is very well in line with the benefit observed for negative and angry facial expressions in previous studies in terms of behavioral indices of sensitivity (Jackson et al , 2008 ; Langeslag et al , 2009 ; Jackson et al , 2014 ; Simione et al , 2014 ; Xie and Shang, 2016 ). An unexpected result refers to the observation that the faces with expression of subtle anger elicited not only an SPCN of lower amplitude than the faces with full expressions of anger but also an SPCN of lower amplitude than the faces with neutral expressions.…”
Section: Discussionsupporting
confidence: 90%
“…Thus there appears to be a natural bias to prioritise attention and processing resources toward threatening rather than positive or rewarding stimuli (e.g. Simione et al, 2014;Maratos, 2011;LeDoux, 2003;Ohman, Lundqvist & Esteves, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…For example, they have been found that high perceptual processing competition (e.g., 150 ms exposure time for encoding) revealed an emotional face advantage (i.e., both happy and angry faces had an advantage over neutral faces). Meanwhile, an angry face advantage emerged when the competition between stimuli was further increased by increasing the stimulus set size (Simione et al, 2014). Furthermore, with the same set size of five, a previous study found a VWM cost for fearful faces compared to neutral faces only with a longer encoding duration (4,000 ms), but it showed no differences with a shorter encoding duration (1,000 ms; Curby et al, 2019: Experiment 1 & Experiment 2).…”
Section: Visual Display Size and Corresponding Timementioning
confidence: 86%
“…However, to the best of our knowledge, no study has summarized the positive and negative face advantages in VWM. Therefore, we have summarized and listed these advantages in the Supplementary Table 1 (including 18 papers), especially on the adoption of the change detection paradigm (Jackson et al, 2008(Jackson et al, , 2009(Jackson et al, , 2012(Jackson et al, , 2014Langeslag et al, 2009;Sessa et al, 2011Sessa et al, , 2018Linden et al, 2011;Becker et al, 2014;Brenner et al, 2014;Simione et al, 2014;Thomas et al, 2014;Maran et al, 2015;Xie et al, 2017;Spotorno et al, 2018;Curby et al, 2019;Lee & Cho, 2019;Liu et al, 2020). We have found that, on the one hand, as we mentioned earlier in introduction, the experimental settings of the change detection and visual search paradigms have much in common.…”
Section: Behavior and Neuroscience Evidence With Different Emotional mentioning
confidence: 95%
See 1 more Smart Citation